Role of Information Component in Adult Education - I. A. Chekin (Научный диалог, 2018)
The article considers the issue of strengthening the role of informational culture of the individual in modern sociocultural conditions. The results of comparative analysis of the main features of the traditional “knowledge” paradigm and the new educational strategy are presented. The characteristics of “knowledge society” and the evolving information society are presented. Definitions of terms “informatization,” “informational society,” “informational culture” are given and substantiated. It is emphasized that the status of knowledge itself changes with the formation of the global information space. Considering the key stages of the new educational strategy, the author uses the categories “information component” and “information approach.” Special attention is paid to the conceptual and methodological aspects of the implementation of the new paradigm in adult education, due to the formation of new functional systems of socio-professional environment in the global informatization. The conditions of organization and development of information environment of vocational education institutions are revealed and concretized. It is concluded that at present there is every reason to talk about the formation of a new informational culture of the individual, which becomes one of the main factors of the formation of a new type of society (including the professional community).